Malaria and missed school days: exploring school absenteeism patterns and local strategies in Odisha, India - Jabir, Muhammed; Panigrahi, Dilip K.; Baig, Muhammad M.; Balakrishnan, Vijayakumar; Panda, Prasant K.; Kumar, Ashwani; Rahi, Manju; Shriram, Ananganallur N. (Frontiers in Public Health, 2025)
BackgroundMalaria continues to pose a significant global health challenge, disproportionately affecting children. While its effects on physical health are well-documented, the impact on education, particularly school absenteeism, remains less understood. This study aimed to explore the influence of malaria on school absenteeism in Odisha, India.MethodsA mixed-methods study was conducted in four southern districts of Odisha from September 2023 to February 2024. This involved a retrospective analysis of school attendance registers from five primary schools and qualitative interviews with 25 school teachers. Statistical analysis was performed using SATA 14.1. Mixed effects logistic regression analysis was used to determine the predictive factors of absenteeism with independent variables such as year, area of school and class. Qualitative data from interviews were transcribed and thematically analyzed.ResultsThe study evaluated absenteeism among 832 children from Class 1 to Class 5 across four academic years (2016–2020), with schools averaging 185 working days annually. While absenteeism rates varied by school, the proportion of students with yearly absenteeism rates of ≥30% remained relatively stable, ranging from 6 to 12.1%. Average absenteeism ranged from 11.5 days in the academic year 2016–2017 to a peak of 22.6 days in 2018–2019. Logistic regression analysis revealed no significant association between malaria endemicity and absenteeism patterns. Schools employed several malaria prevention and case management strategies, including health education, long-lasting insecticidal nets (LLINs), vector control, screening, testing, and on-site treatment. However, resource constraints and cultural barriers continue to pose challenges.ConclusionDespite a decline in malaria cases in the study area, school absenteeism persists due to factors beyond malaria. Future interventions should address these broader socio-cultural and logistical issues to effectively manage absenteeism and improve educational outcomes in malaria-endemic regions.